The Influence of Compensation, Job Satisfaction, and Work Culture on Employee Performance Through Work Motivation AS AN Intervening Variable - M. Raka Mahendra; Zahara Tussoleha Rony; Supardi Supardi (Dinasti Publisher, 2024)
The purpose of this study is to determine the influence of compensation, job satisfaction, and work culture on employee performance through work motivation as an intervening variable at Bank XYZ. The research method used a saturated sample, where the population under study was all employees of Bank XYZ with a total of 120 respondents. Statistical analysis was conducted using Smart PLS 3.2 software and the results are as follows: 1) Compensation has a positive and significant effect on work motivation with a p-Value of 0.002. 2) Compensation has a positive and significant effect on Employee Performance with a p-Value of 0.000. 3) Job Satisfaction has a positive and significant effect on Work Motivation with a p-Value of 0.000. 4) Job Satisfaction does not have a positive and significant effect on Employee Performance with a p-Value of 0.210. 5) Work Culture has a positive and significant effect on Work Motivation with a p-Value of 0.006. 6) Work Culture has a positive and significant effect on Employee Performance with a p-Value of 0.003. 7) Work Motivation has a positive and significant effect on Employee Performance with a p-Value of 0.005. As for the indirect hypotheses: 8) Compensation on Employee Performance through the mediation of Work Motivation obtains a p-Value of 0.037. 9) Job Satisfaction on Employee Performance through the mediation of Work Motivation obtains a p-Value of 0.015. 10) Work Culture on Employee Performance through the mediation of Work Motivation obtains a p-Value of 0.050.